Characterization of Histone Deacetylase Mechanisms in Cancer Development - Hai, Rihan; He, Liuer; Shu, Guang; Yin, Gang (Frontiers in Oncology, 2021)
Over decades of studies, accumulating evidence suggests that epigenetic dysregulation serves as a tumor hallmark. Posttranslational modifications of histones participate in tumor pathogenesis and development mainly through influencing a broad range of physiological processes. Histone deacetylases (HDACs) and histone acetyltransferases (HATs) are pivotal epigenetic modulators, which regulate dynamic processes in the acetylation of histones at lysine residues, thereby influencing transcriptions of oncogenes and tumor suppressor genes. Moreover, HDACs mediate the deacetylation process of many nonhistone proteins, while the latter orchestrate a host of pathological processes such as tumor pathogenesis. In this review, we elaborate on the function of HDACs function in cancer.